REPRESENTATION OF THE FULFILLMENT OF FEMALE REPRESENTATION OF PSI CANDIDATES TOWARDS THE 2024 ELECTION CONTEST IN MEDAN CITY: REPRESENTASI PEMENUHAN KETERWAKILAN PEREMPUAN CALEG PSI MENUJU KONTESTASI PEMILU 2024 DI KOTA MEDAN - Zahra Sari Harahap; Prayetno (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research aims to examine how women's representation in legislative elections is for legislative candidates in the 2024 political contestation. This problem aims to see how the political party, namely the Indonesian Solidarity Party, represents the representation of women legislative candidates in the 2024 legislative election. Contestation in 2024, this is of course It only has a basis, namely that the party that will be studied is the Indonesian Solidarity Party, which is strong in prioritizing equality and is a young party. The type of research used is qualitative descriptive research. The method used in this research is a qualitative research method. The aim of this qualitative research is to understand the conditions of a context by leading to in-depth interviews with various subjects related to the problems raised in this research in detail and in depth regarding a portrait of the condition of the problem being studied, regarding what actually happened according to what happened. in the field of study. The results of the research show that there are many fact interesting that occur in the efforts to fulfill women's representation by the Medan City DPD PSI, so it is ironic that not one female legislative candidate has succeeded in becoming a representative in the Medan City DPRD. The enactment of regulations to realize the presence of women is also just a mere formality which is carried out because of the difficulty of attracting women's hearts and the lack of optimal support from female cadres in political contestation which causes the political world to become powerless and too masculine for women..